Growth and instability in edible oilseeds in India: A temporal analysis: GROWTH AND INSTABILITY IN EDIBLE OILSEEDS IN INDIA: A TEMPORAL ANALYSIS - DINESH; ANWESHA DEY; SHUBHI PATEL; SNIGDHAMANAV (Journal of Oilseeds Research, 2020)
In the field crops section, oilseeds are the second most significant crop after the cereals making them a vital determinant of the agrarian economy. India is one of the leading producer nations of oilseeds globally, but domestic production of edible oil fails to match the rising demands, leading to a considerable rise in the edible oil imports over time. India imports 60 per cent of its annual edible oil requirement. The rich agro-ecological diversity of India is suitable to grow a variety of oilseeds. Once an oil-exporting nation, India has now turned to be an oil-importer country majorly due to widened demand-supply gap, with low productivity being the prime cause for the mismatch. This paper is envisioned to study the growth and instability pattern of edible oilseedsfrom1970-71 to 2017-18. Area observed a declining trend, whereas production showed little growth due to low productivity. Soybean observed the highest growth among seven edible oilseeds. Sunflower showed the highest instability index followed by safflower. Period I exhibited the highest instability, which reduced in further periods as a result of the launch of various oilseed development schemes. Yield effect was the chief contributor to the growth in production of rapeseed-mustard, groundnut, and sesame, whereas area effect boosted the production of soybean, sunflower, safflower, and niger.